Evaluating an Augmented Reality App for Learning About Climate Change among University Students: A Pilot Study - Michel-Acosta, Pamela (2024)
Introduction. The environmental issue has gained unprecedented importance in recent times due to the effects of climate change and the actions of human beings. For this reason, it is very important for future professionals to develop awareness of this situation, while the adoption of emerging technologies, such as augmented reality (AR), which are easy to use and dynamic, encourages active and immersive learning. Aim. This study aims to evaluate the degree of acceptance of undergraduate university students toward AR technology. Methodology. A quantitative pilot study was conducted with a non-probabilistic, intentional sample (N=70) of undergraduate students in the Environment and Culture course at a Dominican university. The applied instrument was the Technology Acceptance Model (TAM), created by Davis in 1989. To analyze the data obtained, the SPSS software was used. Results. The data reflect a high degree of acceptance of AR technology among the participants. The analysis showed the strong reliability of the instrument used. Conclusions. Perceived ease of use, perceived usefulness, and perceived enjoyment positively influenced students’ attitude toward using AR technology and their intention to adopt it. However, the “attitude toward use” dimension demonstrated low reliability.